2006
DOI: 10.2460/ajvr.67.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Effects of femur position on radiographic assessment of completeness of femoral head and neck excision in medium- to large-breed dogs

Abstract: Craniocaudal radiographic views of the femur positioned in external rotation (15 degrees, 30 degrees, and 45 degrees) improved the ability to detect adequacy of excision relative to standard craniocaudal and lateromedial radiographic views. Evaluation of craniocaudal radiographic views of the femur positioned in external rotation may increase the ability to assess FHNE adequacy in medium- to large-breed dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…ClINIC AND SURgERy (ACF) (VINAyAK et al, 2006). After employing this excisional technique, it is necessary to encourage the early use of the limb, to avoid excessive periarticular fibrosis and limitations in movement (DAVIDSON et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…ClINIC AND SURgERy (ACF) (VINAyAK et al, 2006). After employing this excisional technique, it is necessary to encourage the early use of the limb, to avoid excessive periarticular fibrosis and limitations in movement (DAVIDSON et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5]14 Currently, the standard of care is to assess adequacy of the excision with intraoperative palpation of the hip joint for bone contact, and postoperative radiographs consisting of standard orthogonal radiographic views of the pelvis (ventrodorsal and lateromedial). 15 Routine ventrodorsal pelvic radiographic views are obtained with the femurs in extension, with the stifles internally rotated. However, this may obscure the distal medial aspect of the femoral neck, a common site of inadequate resection of FHNE, as the beam is no longer tangential to the excision with internal rotation.…”
Section: Introductionmentioning
confidence: 99%
“…8,16 A radiographic cadaveric study of FHNE in dogs weighing more than 20kg showed that craniocaudal radiographic views with the femur in extension and external rotation (15°, 30°and 45°) dramatically improved the visualization and assessment of adequate ostectomies compared with standard craniocaudal and lateromedial radiographic views. 15 There are anatomical differences in the femurs of cats compared with dogs. Cats have a straighter femur with no isthmus, 14 a shallower acetabulum 17 and the femoral head can have an oval shape as a normal variant.…”
Section: Introductionmentioning
confidence: 99%
“…Femoral head and neck excision (FHNE) is commonly performed to treat painful conditions of the coxofemoral joint including aseptic necrosis of the femoral head, chronic hip luxations, osteoarthritis secondary to hip dysplasia, capital physeal and femoral neck fractures, and non-reconstructable acetabular fractures. 1 The goal of the procedure is to eliminate painful contact between the femur and the acetabulum. It is believed that the most common cause of suboptimal outcome is inadequate removal of the femoral neck resulting in persistent bone contact.…”
Section: Introductionmentioning
confidence: 99%